2015
DOI: 10.1259/bjr.20140168
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for pericardial effusion identified by heart dose–volume histogram analysis in oesophageal cancer patients treated with chemoradiotherapy

Abstract: with oesophageal cancer treated with chemoradiotherapy (CRT) using the following criteria were evaluated: radiation dose .50 Gy; heart included in the radiation field; dose-volume histogram (DVH) data available for analysis; no previous thoracic surgery; and no PCE before treatment. The diagnosis of PCE was independently determined by two radiologists. Clinical factors, the percentage of heart volume receiving .5-60 Gy in increments of 5 Gy (V5-60, respectively), maximum heart dose and mean heart dose were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
5
8
0
Order By: Relevance
“…The rates of PCE development in our study were surprisingly high, with 2-year cumulative incidence of 45.4% in the prospective group and 40.8% in the retrospective group. These findings are supported by previous reports of 27.7% to 52.2% for patients with esophageal cancer (1518), suggesting that PCE may be a common yet underreported toxicity after thoracic RT.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The rates of PCE development in our study were surprisingly high, with 2-year cumulative incidence of 45.4% in the prospective group and 40.8% in the retrospective group. These findings are supported by previous reports of 27.7% to 52.2% for patients with esophageal cancer (1518), suggesting that PCE may be a common yet underreported toxicity after thoracic RT.…”
Section: Discussionsupporting
confidence: 90%
“…This approach is similar to other studies demonstrating associations with whole heart volume (18, 29, 31), although no consensus has been reached regarding which dose-volume variables are truly significant for PCE development. For example, Hayashi et al .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…There are limited data investigating predictors of RP in patients receiving tri-modality therapy for esophageal cancer. Wang et al examined potential predictors of surgical complications in patients receiving tri-modality therapy for esophageal cancer 15 . In their analysis, MLD was strongly associated with increased pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, heart V30 and mean heart dose were individually reported to be associated significantly with PCE by Wei et al[8] and Marks et al [20]. But Hayashi et al [19] suggested that V10 of the heart as the most influential factor. For PE, Shirai et al suggested heart V50 as a useful parameter for assessing the risk of PE but not any DVH parameters of the lung [7].…”
Section: Discussionmentioning
confidence: 99%